2021
DOI: 10.1097/rli.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Algorithm for Fully Automated Detection of Small (≤4 cm) Renal Cell Carcinoma in Contrast-Enhanced Computed Tomography Using a Multicenter Database

Abstract: Objectives: Renal cell carcinoma (RCC) is often found incidentally in asymptomatic individuals undergoing abdominal computed tomography (CT) examinations. The purpose of our study is to develop a deep learning-based algorithm for fully automated detection of small (≤4 cm) RCCs in contrast-enhanced CT images using a multicenter database and to evaluate its performance. Materials and Methods: For the algorithmic detection of RCC, we retrospectively selected contrast-enhanced CT images of patients with histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“… 143 , 144 Toda et al . 145 demonstrated that DL algorithms in contrast-enhanced CT have high accuracy for the diagnoses of SRMs with both internal and external validation. Manual or semi-automated segmentation have been used in most of the studies (either on CT or MRI platforms); Kart et al ., 146 using national databases of whole-body MR imaging from United Kingdom and Germany, developed and trained an automated segmentation DL model for abdominal organs; and Zhao et al 147 clinically assessed assisted compressed sensing technology in renal MRI imaging with an AI algorithm that can adjust scanner settings to improve image acquisition and automatically adjust images to patients’ movements, and can allow ultra-fast MR imaging acquisition.…”
Section: Discussionmentioning
confidence: 98%
“… 143 , 144 Toda et al . 145 demonstrated that DL algorithms in contrast-enhanced CT have high accuracy for the diagnoses of SRMs with both internal and external validation. Manual or semi-automated segmentation have been used in most of the studies (either on CT or MRI platforms); Kart et al ., 146 using national databases of whole-body MR imaging from United Kingdom and Germany, developed and trained an automated segmentation DL model for abdominal organs; and Zhao et al 147 clinically assessed assisted compressed sensing technology in renal MRI imaging with an AI algorithm that can adjust scanner settings to improve image acquisition and automatically adjust images to patients’ movements, and can allow ultra-fast MR imaging acquisition.…”
Section: Discussionmentioning
confidence: 98%
“…During the last 10 years, machine learning, and in particular deep convolutional neural networks (DCNNs), have gained considerable popularity in medicine and radiology for disease detection, image reconstruction, and tissue segmentation, which was accompanied by an almost exponential increase in the number of peer-reviewed publications. [34][35][36][37][38][39][40] The increase in research output and development of clinical applications was fueled by the development of DCNNs and the broadening availability of high-performance computer systems with powerful graphical processing units. Furthermore, the accessibility of open-source deep learning (DL) toolkits provided access to a worldwide community for exploring and performing research on this topic with limited expert knowledge requirements in artificial intelligence (AI) and computer sciences.…”
Section: Artificial Intelligence-based Machine Learning For Musculosk...mentioning
confidence: 99%
“…During the last 10 years, machine learning, and in particular deep convolutional neural networks (DCNNs), have gained considerable popularity in medicine and radiology for disease detection, image reconstruction, and tissue segmentation, which was accompanied by an almost exponential increase in the number of peer-reviewed publications 34–40 . The increase in research output and development of clinical applications was fueled by the development of DCNNs and the broadening availability of high-performance computer systems with powerful graphical processing units.…”
Section: Artificial Intelligence–based Machine Learning For Musculosk...mentioning
confidence: 99%
“…Promising results have already been obtained for several diseases such as bone tumors, 12 prostate cancer, 13 and kidney cancer. 14 In addition, DL models could help radiologists in their daily practice. Recently, an algorithm for breast cancer detection significantly decreased the false-positive and false-negative rates on 2 large data sets, while substantially reducing the radiologists' workload.…”
mentioning
confidence: 99%
“…Given this context, deep learning (DL) methods could play an important role to assist with diagnosis, by issuing alerts for patients at risk of pancreatic cancer. Promising results have already been obtained for several diseases such as bone tumors, 12 prostate cancer, 13 and kidney cancer 14 . In addition, DL models could help radiologists in their daily practice.…”
mentioning
confidence: 99%